PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BIRO UMUM SEKRETARIAT DAERAH PROVINSI SULAWESI TENGGARA - Reski Setiawandika; Adnan Hakim; Sri Wiyati Mahrani (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to (1) determine and analyze the effect of work motivation, work discipline and work involvement on employee performance at the General Secretariat Office of the Southeast Sulawesi Province. (2) To determine and analyze the effect of work motivation on employee performance at the General Bureau of the Regional Secretariat of Southeast Sulawesi Province. (3) To find out and analyze the effect of work discipline on employee performance at the General Bureau of the Regional Secretariat of Southeast Sulawesi Province. (4) To find out and analyze the effect of work involvement on employee performance at the Office of the General Bureau of the Regional Secretariat of Southeast Sulawesi Province.The design of this study used an explanatory research design (Explanatory Research). This study uses a survey research approach that uses sample data by distributing questionnaires (questionnaires). The size of this research sample is determined by using the Slovin formula, then a sample of 75 people is obtained. The sampling technique used was Stratified Random Sampling. To calculate the sample each Stratified using the proportional formula.The results showed that work motivation partially had a positive and significant effect on employee performance. Then work discipline partially positive and significant effect on employee performance. Good work involvement is proven to have a positive and significant effect on improving employee performance. Thus it can be concluded that changes in work motivation, work discipline, and work involvement which are reflected through the need for achievement, compliance with rules, and considering work as something important have a positive and significant contribution together to improve performance. employees as reflected in quantity, quality, time, cost, service orientation, commitment, work initiative, and cooperation.